Optimization of the maximum likelihood estimator for determining the intrinsic dimensionality of high-dimensional data - Karbauskaite, Rasa; Dzemyda, Gintautas (Zielona Góra: Uniwersytet Zielonogórski)
One of the problems in the analysis of the set of images of a moving object is to evaluate the degree of freedom of motion and the angle of rotation. Here the intrinsic dimensionality of multidimensional data, characterizing the set of images, can be used. Usually, the image may be represented by a high-dimensional point whose dimensionality depends on the number of pixels in the image.
Keywords: multidimensional data; intrinsic dimensionality; maximum likelihood estimator; manifold learning methods; image understanding